Sifat Kayu Lapis yang Dibuat dari Lima Jenis Kayu Asal Riau - Achmad Supriadi; Deazy Rachmi Trisatya; Ignasia Maria Sulastiningsih (Jurnal Ilmu Pertanian Indonesia, 2020)
The objective of this study was to determine the physical and mechanical properties of plywood made of punak (Tetramerista glabra Miq.), meranti bunga (Shorea teysmanniana Dyer ex Brandis), mempisang (Alphonsea spp.), suntai (Palaqium burckii H.J.L.), and pasak linggo (Aglaia argentea Blume). Liquid urea formaldehyde (UF) was used as an adhesive. Data analysis was carried out using a completely randomized design. Results showed that the moisture content and density of plywood produced in this study were around 10.4-10.95% and 0.65 to 0.93 g/cm3, respectively. The modulus of elasticity (MOE) and modulus of rupture (MOR) of plywood produced were between 63.371-123.548 kg/cm2 and 517-1.052 kg/cm2, respectively. It was also found that the tensile strength and bonding strength of the plywood produced were 461.6-1.095 kg/cm2 and 18.97-31.79 kg/cm2, respectively. It was recorded that moisture content and the bonding strength of the plywood produced met the Indonesian National Standard of Plywood. Among others, plywood produced from pasak linggo showed a superior quality. Referring to statistical analysis, it was confirmed that physical and mechanical properties of plywood were significantly affected by wood species, except moisture content. Keywords: mechanical properties, physical properties, plywood, Riau wood species